Problems of ensuring authenticity of texts in Kazakh and Russian in the Civil Procedure Code of the Republic of Kazakhstan - Ilyassova, G.A. (Bulletin of the Karaganda University “Law Series”, 2022)
The article analyzes the results of linguistic and legal expertise of texts in Kazakh and Russian of the Civil Procedure Code of the Republic of Kazakhstan within the framework of the topic of scientific research. The author draws attention to inappropriate translations of legal terms that are incomprehensible in the meaning of the rule of law in the text of this law, which were fixed in the law as a result of incorrect translation of sentences into Kazakh. The purpose of the research is to identify inconsistencies in the translation of legal terms based on the results of a comparative linguistic and legal expertise to ensure the authenticity of the texts of the Civil Procedure Code of the Republic of Kazakhstan in Kazakh and Russian languages, as well as to provide the correct translation of legal terminology. The unified unified dictionary of legal terms in the Kazakh language has not been adopted, therefore, the texts of laws are translated using various terms, and this leads to an erroneous understanding of the norms of law. The results of the study prove that by increasing the status of the state language, it is possible to ensure the quality of laws, in addition, it is necessary to form an effective mechanism for the application of legal technology by identifying problems in the theory and practice of ensuring the quality of civil legislation in the state language. The author comes to the conclusion that in order to ensure the uniformity of legal terms, it is important to compile a unified dictionary of legal terms in the state language.